The invention of science : a new history of the scientific revolution / David Wootton. - Wootton, David, 1952- (Allen Lane, 2015)
We live in a world made by science. How and when did this happen? This book tells the story of the extraordinary intellectual and cultural revolution that gave birth to modern science, and mounts a major challenge to the prevailing orthodoxy of its history.